Determination of Silage Quality of Alfalfa and Annual Ryegrass Mixture - Abdurrahman Alper DÜNDAR; Hanife MUT (ISPEC Journal of Agricultural Sciences)
Animal feed often includes cereal straw and forage crops. Silage is a traditional process practiced ensiliation of seasonally harvested forage or some crops, ensuring a constant supply of feed for animals. In this study, which was carried out to determine the quality of silages made of alfalfa and annual ryegrass in plain and different mixture ratios in Bilecik conditions. This study was carried out to determine the silage quality of alfalfa and Italian ryegrass mixtures (100:0, 80:20, 60:40, 40:60, 20:80 and 0:100). The harvested plants were cut into 2 cm size after wilting a little and filled into 2 kg vacuum silage packages considering the mixing ratios. The silage samples, whose air was removed by vacuum packaging machine and their mouths were closed, were stored at 25±2 oC for 45 days. In treatments were determined physical observations, dry matter rate, pH, crude protein rate, acid detergent fiber rate, neutral detergent fiber rate, relative feed value, acetic acid, lactic acid and some mineral contents. As a result, it was determined that annual ryegrass added to alfalfa at different rates positively affected silage quality. Considering all the examined characters, it was found that adding 40 – 80 % annual ryegrass to the alfalfa silage as better results in terms of silage quality.